Answer:
See below.
Step-by-step explanation:
To establish the inverse of a logarithmic function, first swap the x and y variables in the original function. Then, solve the resulting equation for y, and finally express y as f⁻¹(x). The resulting function will be an exponential function with the same base as the base of the original logarithmic function.
[tex]\dotfill[/tex]
As an example, let's find the inverse of y = 2log₃(x - 4).
First, swap the x and y variables:
[tex]\large\text{$x=2\log_3(y-4)$}[/tex]
Now, solve the equation for y:
[tex]\large\text{$\dfrac{x}{2}=\log_3(y-4)$}\\\\\\\large\text{$3^{\frac{x}{2}}=3^{\log_3(y-4)}$}\\\\\\\large\text{$3^{\frac{x}{2}}=y-4$}\\\\\\\large\text{$y=3^{\frac{x}{2}}+4$}[/tex]
Finally, express y as f⁻¹(x):
[tex]\large\text{$f^{-1}(x)=3^{\frac{x}{2}}+4$}[/tex]